COLOUTERINE FISTULA WITH A FOREIGN BODY - Islam, Aliya; Arif, Sadia (Journal of Ayub Medical College Abbottabad, 2010)
Foreign bodies in vagina are known to have been inserted by the patient herself or by some other person; as an aid to masturbation, sexual intercourse or sexual assault. The two most common items retained in adult females are tampons and burst condoms. Since long, vaginal deliveries and Obstetric and Gynaecological interventions have been associated with vesicovaginal and rectovaginal fistulae. We present a case of a 24 years old Pakistani woman with a colouterine fistula. Although vesicouterine fistulae have rarely been reported previously, world-literature has only a few documented cases of colouterine fistula. Keywords: Colouterine fistula, fistula, primary repair